PUSAT BUKU SEBAGAI RUANG PUBLIK DENGAN KONSEP REKREATIF DAN INFORMATIF DI SURAKARTA - Yusna Primastuti; Rachmadi Nugroho; Amin Sumadyo (ARSITEKTURA, 2016)
"Books are the windows to the world" is a very common phrase heard. There are so many benefits to be gained from reading the books. From the books, the readers can get information, knowledge, or even a new experience very rewarding. But what is happening now is the public interest of Indonesians is still relatively low. Indonesia’s rank only third from bottom in the ASEAN region. Many people are lazy to go to the libraries and the bookstores because it is considered boring. Therefore, the existence of a book center which is more recreational as a reading place becomes necessary. From these issues, the problem that appears is how to design an expression of space and shape of the building that accommodates the activities of libraries to the concept of a recreational and informative to then be translated into the design Book Centre in Surakarta. The method used in the form of architectural design methods, ranging from data collection and then analyzed based on functional programming, programming performance and architectural analysis. Recreational and Informative concept applied to the shape of the building and expression of space in this Book Center, so it can bring the design of the building that can accommodate all the activities related to the book include reading, information, distribution, promotion, socialization, and discussion to fulfill the people’s need of books and also as a public space to create social interaction for them. Book Centre is planned to be more recreational and informative so as can attract people to come and to increase public interest of reading book which is still very low in a pleasant atmosphere by displaying the characteristic of recreational and informative. Book Centre with all the activities that take place in it will be able to provide information that is explanatory, instructive, stimulating, persuasive, and can provide refreshment and comfort for the people, so it will increase the interest in reading books and increase knowledge for the visitors. Keywords: Book Center, Informative, Public Space, Recreational.